Tren COVID-19 dan pembatasan mobilitas penduduk - Haning Romdiati; Mita Noveria (Jurnal Kependudukan Indonesia, 2021)
The Indonesian government has imposed policies of restricting population mobility to control COVID-19 transmission. Several population mobility regulations have been implemented, which were heavily affected by fluctuation in COVID-19 positive cases. This paper discusses trends in population mobility due to various policies related to population mobility restriction, nationally and locally. Analyses were based on secondary data, including population mobility restriction policies and trends in the number of COVID-19 cases since the government has formally declared the peak of the second wive at mid-2021. Data on the number of airplane passengers departing from and arriving at Soekarno-Hatta airport from March 2020 to August 2021 was also used. The results of the analysis show that the trend of passengers’ mobility during the COVID-19 pandemic was influenced by government policy on transportation, referring to the fluctuation of the daily number of positively confirmed COVID-19 cases. In the case of increasing of the positive cases, the government issued a policy on tightening aircraft passenger requirements which resulted in a decreasing number of passengers, and vice versa. Currently, the increase in COVID-19 cases shows the sloping trend, but efforts to control its transmission, including population mobility restriction, must still be carried out.